Servant leadership’s impact on trust, commitment, and performance in higher education - Adison Adrianus Sihombing; Eliana Sari; Hafid Abbas; Maifalinda Fatra (Institute of Advanced Engineering and Science, 2024)
This research examined the relationship between servant leadership (SL), organizational trust (OT), organizational commitment (OC), and task performance (TP). It employed a quantitative research design with partial least squares-structural equation modeling (PLS-SEM) and bootstrap estimation. Data were collected through a survey of 111 lecturers from 12 universities in Eastern Indonesia. It found that SL does not affect TP and OC. Meanwhile, OT affects OC but not TP. Further, OC does not affect TP. Therefore, OT does not affect TP through OC. Likewise, SL does not affect TP through OC. It practically implies that universities should be concerned the selection and placement of professional leaders. Successful professional leaders support and enhance the OC and TP of lecturers with SL. This study enriches leadership literature empirically examining SL, TP, OT, and OC in religious higher education. Besides, it provides evidence that SL in tertiary institutions does not exhibit a positive impact on lecturer performance. Institutional limitations lead to difficult situations and allow lecturers to accept reality. Furthermore, it uncovers challenges and demands the need for in-depth investigation of SL studies, which are paradoxical and contradictory to the previous SL theories and findings.